Adult-onset Still's disease: Clinical cases - G. R. Imametdinova; N. V. Chichasova (Современная ревматология)
The annual incidence of adult-onset Still's disease (AOSD) worldwide is 0.16 cases per 100,000 persons. Its leading symptoms are joint involvement, fever, skin rash, and neutrophilic leukocytosis in the absence of rheumatoid factor and anticyclic citrullinated peptide antibodies in serum and synovial fluid. In its initial stage, there may be monoarthritis more commonly of the wrist, hip, or knee. Then the lesion assumes the pattern of oligo- or polyarthritis. Musculoskeletal involvement appearing as arthralgia, arthritis, and myalgia is noted in all patients. In the majority of patients, articular involvement progresses and destructive polyarthritis develops. Symmetric involvement of the carpophalangeal and distal interphalangeal joints is frequently detected. Skin lesion manifests itself as maculopapular or roseolous rashes on the chest, back, shoulders, occasionally on the legs, or in the areas of mechanical irritation. A sore throat with the signs of pharyngitis is a characteristic early symptom of the disease. There may be involvements of the liver, cardiovascular system, lung, as well as lymphadenopathy, or splenomegaly. The chronic course of the disease is more frequently noted.The paper describes two cases of AOSD. One case demonstrates that the physician has no experience in diagnosing and managing patients with AOSD, resulting in the misinterpretation of the increase in disease activity when the subclinical doses of methotrexate (MT) are used, which has been regarded as a therapeutic complication. The use of the adequate dose of MT could achieve a clinical and laboratory remission and discontinue glucocorticoids (GC).In the other case of recurrent AOSD and mild clinical symptoms, the unreasonable use of high GC doses gave rise to adverse reactions.